Comparıson Of Productıon And Income Of Organıc Rıce Farmers Wıth Conventıonal Rıce In The Horseshoe Regıon - Evita Soliha Hani; Sigit Soeparjono; Roni Yulianto; Wildan Muhlison; Tri Wahyu Saputra; Laily Ilman Widuri; Fariz Kustiawan Alfarisy (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The agricultural system in rice farming in the Horseshoe region of East Java Province is conventional and organic. This study aims to identify rice farmers' understanding of organic farming systems, to analyze differences in conventional and organic rice production systems and to analyze differences in income between conventional and organic rice farmers. The method of determining the research area carried out in Bondowoso, Jember, and Lumajang Regencies in the Horseshoe Region in East Java was purposive. The number of respondents was carried out randomly in organic and conventional farmers and the determination of respondents used the accidental method. Primary data collection by way of interviews, while secondary data by way of observation, documentation and heritage studies. Frequency tables are needed to describe farmers' understanding of organic rice farming systems and independent differential tests to compare production and income of the two rice farming systems.